Disaster resilience and complex adaptive systems theory: Finding common grounds for risk reduction. Issue 2 (4th April 2016) - Coetzee, Christo; Van Niekerk, Dewald; Raju, Emmanuel
Abstract : Purpose: – The purpose of this paper is to explore the emergence of resilience into the contemporary discourse of disaster risk. As a counter position to the current status quo in defining and addressing resilience, this paper introduces the theoretical lens of complex adaptive systems theory (CAS). Some of the key characterisitcs related to CAS are discussed and linkages are made to possible benefit that they might have in enhancing the understanding of disaster resilience. Design/methodology/approach: – An indepth review of literature pertaining to disaster resilience and CAS was conducted to find common grounds for theoretical synergies. Findings: – The inherent similarities between the concept of resilience and CAS provides ample practical and theoretical contributions to the field of disaster risk studies. Originality/value: – The paper provides a different perspective to the contemporary discourse on disaster resilience. A better understanding of disaster resilience and its underlying dynamics as illuminated by the application of CAS could in future provide an effective tool to manage disaster risks and building of resilience.